1978
DOI: 10.1056/nejm197801192980302
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Function in Experimental Renal Disease by Dietary Restriction of Phosphate

Abstract: We sought to determine the importance of calcium phosphate deposition in the functional deterioration of damaged or diseased kidneys. Using the remnant-kidney model in rats, we found that dietary phosphate restriction prevented proteinuria, renal calcification, histologic changes, functional deterioration and death in uremia. Histologic examination of the remnant kidney in the nonrestricted animals showed calcium and phosphorus deposits in the cortical tubular cells, basement membranes and interstitium. A simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
2

Year Published

1980
1980
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(91 citation statements)
references
References 14 publications
7
82
2
Order By: Relevance
“…Low calcitriol levels are hypothesized to decrease cardiac contractility and to contribute to arteriosclerosis and endothelial dysfunction (51,52). In addition, clinical and experimental data indicate that high serum phosphate levels and phosphate loading may accelerate the progression of CKD (12,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Low calcitriol levels are hypothesized to decrease cardiac contractility and to contribute to arteriosclerosis and endothelial dysfunction (51,52). In addition, clinical and experimental data indicate that high serum phosphate levels and phosphate loading may accelerate the progression of CKD (12,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Multiple case reports and controlled human studies 5-7,24 -26 demonstrated that receipt of a standard regimen of OPS (which contains approximately six times the average daily phosphate intake) results in acute rises in serum phosphate. Moreover, data in rat models of CKD (remnant kidney and nephrotoxic serum nephritis) demonstrate that higher levels of dietary phosphate accelerate loss of kidney function 10,11 and that this effect is attenuated by administration of phosphate binders. 12,13 Despite this plausible link, our data do not support an association between receipt of OPS and kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, high dietary phosphorus has been shown to initiate and/or worsen progression of kidney dysfunction (26), whereas dietary phosphate restriction reverses and/or restricts the dysfunction (27). Although the most common explanation has been phosphorus-induced calcification, there are other potential proposed mechanisms including phosphorus-dependent podocyte injury due to overexpression of pituitary-specific positive transcription factor 1 (Pit-1) transporter in rats (28).…”
Section: Association Between Serum Phosphorus and Progression Of Kidnmentioning
confidence: 99%